2003
DOI: 10.1099/vir.0.18834-0
|View full text |Cite
|
Sign up to set email alerts
|

Oral immunization with recombinant Yersinia enterocolitica expressing a measles virus CD4 T cell epitope protects against measles virus-induced encephalitis

Abstract: Immunization via the oral route with an attenuated Yersinia enterocolitica strain expressing a fragment of the measles virus nucleocapsid protein (aa 79-161) via its type III protein secretion system induced a T helper type 1 response in immunized C3H mice, which conferred protection against measles virus-induced encephalitis in a time-and dose-dependent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Published studies have well established the role of MHC class I molecules in activating antiviral immunity as well as the evolution of numerous viral strategies to thwart the class I pathway (29,40). Yet, the importance of MHC class II molecules in protective immunity against live viruses is also documented (6,7,41). Thus, an increasing number of studies also point to viral disruption of MHC class II Ag presentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Published studies have well established the role of MHC class I molecules in activating antiviral immunity as well as the evolution of numerous viral strategies to thwart the class I pathway (29,40). Yet, the importance of MHC class II molecules in protective immunity against live viruses is also documented (6,7,41). Thus, an increasing number of studies also point to viral disruption of MHC class II Ag presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Such presentation is central to initiate primary, cellular immune responses as well as to establish efficient, durable secondary immune responses (1,2). Although long known to mediate protective immunity to bacteria and toxins, the important roles of CD4 ϩ T cells in tumor immunity and viral clearance have also been well established (3)(4)(5)(6)(7).…”
mentioning
confidence: 99%
“…has also been exploited for foreign antigen delivery (39,55,116). Upon bacterial contact with a eukaryotic cell, the Salmonella type III secretion system creates a hypodermic needlelike apparatus that spans the bacterial envelope and "injects" proteins from the bacteria into the host cell.…”
Section: Location Location Locationmentioning
confidence: 99%
“…In addition to the enteric pathogens discussed above, other bacteria being considered as live vectors include Yersinia enterocolitica (55), Y. pseudotuberculosis (115), Bordetella bronchiseptica, and B. pertussis (129). The mucosal commensals such as Streptococcus gordonii (85) and the lactic acid bacteria (54, 100) such as the Lactococcus and Lactobacillus spp.…”
Section: Other Bacterial Vectorsmentioning
confidence: 99%
“…(116) Immunization via the oral route with an attenuated Yersinia enterocolitica strain expressing a fragment of measles virus nucleocapsid protein (amino acid 79-161) induced a T-helper type I response in immunized C3H mice, which conferred protection against measles virus-induced encephalitis in a time-and dose-dependent manner. (117) Recent studies have reported successful use of aerosol measles vaccine in different clinical setups. (118,119) Tuberculosis Mycobacterium tuberculosis (MTB) is the most-common cause of tuberculosis though Mycobacterium bovis and Mycobacterium africanum are also occasionally implicated.…”
Section: Measlesmentioning
confidence: 99%